Exponential stability estimate for the derivative nonlinear Schrödinger equation*Supported by NNSFC Nos. 11671066, 12071053 and NSFSP No. ZR2019MA062. (5th May 2022) - Cong, Hongzi; Mi, Lufang; Wu, Xiaoqing; Zhang, Qidi
Abstract: In this paper, we prove an exponential long time stability result for the derivative nonlinear Schödinger equation (DNLS) in some Sobolev space by using Birkhoff normal form technique and some suitable nonresonant conditions.